2005
DOI: 10.1002/rcm.1961
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of 23‐hydroxybetulinic acid in mouse plasma using electrospray liquid chromatography/mass spectrometry

Abstract: 23-Hydroxybetulinic acid is a newly isolated derivative of betulinic acid. The agent exhibits potential anti-tumor activity and functions in this regard via apoptosis. In support of pharmacokinetic and toxicological evaluations, a new assay based on liquid chromatography/mass spectrometry (LC/MS) was developed for the quantitative analysis of 23-hydroxybetulinic acid. Sample preparation consisted of extraction of the plasma by the addition of methylene chloride followed by centrifugation. Aliquots of the super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…There was no significant reduction of the body weight in nude mouse after treatment with BBA at effective reversal concentration of 15 mg/kg [22]. Although the plasma concentration of BBA was not determined in the previous nude mouse study, the plasma concentration of 23-HBA (the compound from which BBA was synthesized) was reported, where 23-HBA at 2 h attained a C max of 3.1 µg/ml (=6.56 µM) after intragastric administration (IG) of 200 mg/kg 23-HBA [48]. Nevertheless, the potential of BBA to be developed into an adjuvant to chemotherapy still needs to be further investigated, where the clinically effective plasma concentration, drug interaction and pharmacokinetics of BBA in combination with chemotherapeutic agents in vivo needs to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant reduction of the body weight in nude mouse after treatment with BBA at effective reversal concentration of 15 mg/kg [22]. Although the plasma concentration of BBA was not determined in the previous nude mouse study, the plasma concentration of 23-HBA (the compound from which BBA was synthesized) was reported, where 23-HBA at 2 h attained a C max of 3.1 µg/ml (=6.56 µM) after intragastric administration (IG) of 200 mg/kg 23-HBA [48]. Nevertheless, the potential of BBA to be developed into an adjuvant to chemotherapy still needs to be further investigated, where the clinically effective plasma concentration, drug interaction and pharmacokinetics of BBA in combination with chemotherapeutic agents in vivo needs to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the accurate mass data, the structures of metabolites can be characterized and identified accurately and quickly. Although the fragments of limonin and obacunone have been reported under electron ionization (EI)‐MS conditions, their fragmentation by electrospray ionization tandem mass spectrometry (ESI‐MS/MS) should be studied comprehensively, because of the large number of determinations using ESI …”
mentioning
confidence: 99%
“…The reason may be due to the failure to ionize low polarity triterpenoid compounds by ESI and/or the absence of prominent product ions during collision‐induced dissociation. This has been illustrated by reported LC/MS methods for quantifying pentacyclic triterpenoids such as betulinic acid, 23‐hydroxybetulinic acid and ursolic acid from biological fluids . Further, a recent work on LC/MS revealed that an ESI source was insensitive to analysis of triterpene compounds …”
mentioning
confidence: 99%
“…This has been illustrated by reported LC/MS methods for quantifying pentacyclic triterpenoids such as betulinic acid, 23-hydroxybetulinic acid and ursolic acid from biological fluids. [25][26][27] Further, a recent work on LC/MS revealed that an ESI source was insensitive to analysis of triterpene compounds. [28] In the present work, a sensitive, selective and reproducible HPLC/ESI-MS/MS method has been developed for quantification of AA using colchicine as internal standard (IS) from rat plasma.…”
mentioning
confidence: 99%